Analisis Percepatan Simulasi Tumbukan Airbag Kendaraan Berbasis Mikrokontroler Dengan Sensor ADXL345 dan FC-51 - Yuniarto Agus Winoko; Ali Fauzan Kurnia; Ratna Monasari; Akbar Anugrah Ikhsani (Infotekmesin, 2026)
Delays or failures in airbag system activation can have fatal consequences for driver safety, thus requiring a collision detection mechanism with a high degree of precision and reliability. This study aims to design and evaluate an experimental testbed to analyze the characteristics of impact acceleration as the primary trigger parameter in airbag activation systems. The collision dynamics simulation was represented through the implementation of the sled test method using a data acquisition system that integrates an ADXL345 accelerometer, which had undergone precision validation via a six-position tumble test on 100 reference samples, and an FC-51 infrared sensor specifically calibrated for measuring the distance and velocity of objects. Based on vehicle dynamics literature, which refers to a deceleration range of 3g to 5g at speeds of 16–24 km/h, the threshold configuration for actuation is set at an acceleration of 40 to 46 m/s². The results of the instrumentation performance tests showed good data reading stability, with an average sensor noise fluctuation level of 3.5 m/s². A comparative statistical analysis using a two-sample t-test on two impact velocity variations demonstrated a mathematically highly significant difference in acceleration, with a p-value = 0.000. The airbag simulation developed demonstrates a high level of reliability in precisely identifying impact forces in accordance with threshold parameters. This study concludes that experimental methods are highly effective for characterizing airbag activation trigger parameters, but further research is needed to comprehensively evaluate airbag response performance.